Simultaneous PAHs degradation, odour mitigation and energy harvesting by sediment microbial fuel cell coupled with nitrate-induced biostimulation. (15th April 2021) - Zhang, Zhen; Zhang, Kun; Ouyang, He; Li, Marcus K.K.; Luo, Zifeng; Li, Yongtao; Chen, Chengyu; Yang, Xingjian; Shao, Zhiwei; Yan, Dickson Y.S.
Abstract: The study investigates a bioremediation process of polycyclic aromatic hydrocarbons (PAHs) removal and odour mitigation combined with energy harvesting. Sediment microbial fuel cells (SMFCs) were constructed with the addition of nitrate in the sediment to simultaneously remove acid-volatile sulphide (AVS) and PAHs. With the combined nitrate-SMFC treatment, over 90% of the AVS was removed from the sediment in 6 weeks of the SMFC operation and a maximum of 94% of AVS removal efficiency was reached at Week 10. The highest removal efficiencies of phenanthrene, pyrene, and benzo[a]pyrene was 93%, 80%, and 69%, respectively. The maximum voltage attained for the combined nitrate-SMFC treatment was 341 mV. Illumina HiSeq sequencing revealed that the autotrophic denitrifiers Thiobacillus are the dominant genus. In electricity generation, both sulphide-oxidation and PAH-oxidation are the possible pathways. Besides, the addition of nitrate stimulated the growth of Pseudomonas which is responsible for the electricity generation and direct biodegradation of the PAHs, indicating a synergistic effect. The developed bioremediation process demonstrated the potential in the in-situ bioremediation process utilizing SMFC combined with nitrate-induced bioremediation. Graphical abstract: Image 1 Highlights: Sediment microbial fuel cells could simultaneously remove AVS and PAHs. The maximum voltage attained for the combined nitrate-SMFC treatment was 341 mV. Nitrate addition stimulated the growth of Pseudomonas and enhanced the electricity generation and biodegradation effects.